PENERAPAN METODE PECS (PICTURE EXCHANGE COMMINICATION SYSTEM) DALAM MENINGKATKAN KEMAMPUAN KOMUNIKASI RESEPTIF ANAK AUTIS - Nurjuliani, Agis; Dedi Mulia; Sistriadini Alamsyah Sidik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the receptive communication skills of a child with autism at Phase A level at SKh PGRI Rangkasbitung through the use of the Picture Exchange Communication System (PECS) method. This research employed an experimental approach using Single Subject Research (SSR) with an A–B–A design. The subject of this study was one SDKh student with autism. The target behavior in this study was the child's ability to understand simple instructions and respond to commands through the selection of appropriate picture cards. Data were collected through observation and performance-based tests, while data analysis was conducted using descriptive statistical analysis presented in graphical form. The results showed that the average receptive communication ability of the subject in baseline 1 (A1) was 33%, indicating the child's initial condition before the intervention. During the intervention phase (B), the average receptive communication ability increased to 90% after the subject received treatment using the PECS method. Furthermore, in baseline 2 (A2), the average receptive communication ability was 53%, reflecting the subject's natural ability after the intervention was withdrawn. Based on these findings, it can be concluded that the PECS (Picture Exchange Communication System) method is effective in improving the receptive communication skills of children with autism, particularly in understanding instructions and responding to commands through picture card media among SDKh level students at SKh PGRI Rangkasbitung.